RESPON AUDITOR TERHADAP KEBERADAAN TRANSAKSI E-COMMERCE - SALLY BERNADETHA VINCENTIA (Universitas Katolik Widya Mandala Surabaya, 2012)
E-commerce seems to do more and more companies and consumers as a result of the benefits held good for both parties involved in the transaction. E-commerce to bring influence to the world of business, including the audit function in carrying out the task they have. The existence of e-commerce transactions is to bring the virtual, where companies and consumers are not met physically, but through the internet facility. This causes difficulties internal and external auditors to obtain authentic evidence to declare the existence of fraud or financial irregularities. Auditors seem to clean up by providing an appropriate response to the presence of e-commerce. Auditor's ability to respond to both the e-commerce, while running existing functions have led to the ability to continue to provide benefits because they still have the competence despite environmental changes due to e-commerce.